Marriage of Virus‐Mimic Surface Topology and Microbubble‐Assisted Ultrasound for Enhanced Intratumor Accumulation and Improved Cancer Theranostics. Issue 13 (14th May 2021) - Meng, Zheying; Zhang, Yang; Shen, E; Li, Wei; Wang, Yanjie; Sathiyamoorthy, Krishnan; Gao, Wei; C. Kolios, Michael; Bai, Wenkun; Hu, Bing; Wang, Wenxing; Zheng, Yuanyi
Abstract: The low delivery efficiency of nanoparticles to solid tumors greatly reduces the therapeutic efficacy and safety which is closely related to low permeability and poor distribution at tumor sites. In this work, an "intrinsic plus extrinsic superiority" administration strategy is proposed to dramatically enhance the mean delivery efficiency of nanoparticles in prostate cancer to 6.84% of injected dose, compared to 1.42% as the maximum in prostate cancer in the previously reported study. Specifically, the intrinsic superiority refers to the virus‐mimic surface topology of the nanoparticles for enhanced nano–bio interactions. Meanwhile, the extrinsic stimuli of microbubble‐assisted low‐frequency ultrasound is to enhance permeability of biological barriers and improve intratumor distribution. The enhanced intratumor enrichment can be verified by photoacoustic resonance imaging, fluorescence imaging, and magnetic resonance imaging in this multifunctional nanoplatform, which also facilitates excellent anticancer effect of photothermal treatment, photodynamic treatment, and sonodynamic treatment via combined laser and ultrasound irradiation. This study confirms the significant advance in nanoparticle accumulation in multiple tumor models, which provides an innovative delivery paradigm to improve intratumor accumulation of nanotherapeutics. Abstract : This work proposes the combination of intrinsic optimization the nanostructure as virus‐mimic surface topology to enhance nano–bio interactions and extrinsic stimuli of microbubble‐assisted low‐frequency ultrasound to vastly improve intratumor permeability and distribution of nanoparticles in multiple cancer models. The multifunctional nanoplatform is capable with trimodal imaging to determine the optimal therapeutic timing, which demonstrates a successful combined anticancer effect.